ORGANIZATIONS AND ALLIANCES IN CENTRAL ASIA: OOPERATION PROSPECTS AS SEEN FROM MOSCOW AND LONDON - MOROZOV, Yuri; McDERMOTT, Roger (CENTRAL ASIA AND THE CAUCASUS, 2008)
Between 29 April and 1 May, 2008 we attended an international conference that discussed Central Asian security issues. Political scientists and politicians from 17 countries and several international structures gathered in Tashkent for this highly representative forum to assess the already obvious threats to Central Asian security; discuss the new and less obvious threats and challenges; and outline potential cooperation trends aimed at ensuring regional security in the 21st century.The authors, who by citizenship belong to the member states of “organizations and alliances that follow different vectors,” have taken the trouble of showing the road toward their countries’ potential partnership in the key regional stability spheres. They deliberately avoided agitation and propaganda either of the “pro-Russian” or “pro-Western” security vectors in Central Asia to insist that cooperation rather than rivalry among the main actors present in the region can finally produce a security system that will meet the national interests of the regional states and of the world community as a whole. This is an economically justified and civilized pattern of international relations.